2019
DOI: 10.1126/scitranslmed.aaw6419
|View full text |Cite
|
Sign up to set email alerts
|

Control of cytokinesis by β-adrenergic receptors indicates an approach for regulating cardiomyocyte endowment

Abstract: One million patients with congenital heart disease (CHD) live in the United States. They have a lifelong risk of developing heart failure. Current concepts do not sufficiently address mechanisms of heart failure development specifically for these patients. Here, analysis of heart tissue from an infant with tetralogy of Fallot with pulmonary stenosis (ToF/PS) labeled with isotope-tagged thymidine demonstrated that cardiomyocyte cytokinesis failure is increased in this common form of CHD. We used single-cell tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 85 publications
(138 reference statements)
6
80
0
2
Order By: Relevance
“…Mlc2v cre :Ect2 flox/flox mutants had an increase in the mean ratio of BiNucs to MoNucs at P3 of 0.901 ± 0.08 compared to 0.339 ± 0.02 in control mice ( Figures 7C and 7D). This result agrees with recent work by Liu et al (2019), which also showed that the loss of Ect2 results in an increase in BiNucs during the neonatal period and that increased expression of Ect2 leads to increased MoNucs. qPCR revealed a significant decrease in the expression of E2f target genes in Mlc2v cre : Ect2 flox/flox mutants compared to controls, but no significant change in genes that are not E2f targets ( Figure 7E).…”
Section: Binucleation Directly Results In the Downregulation Of E2f Tsupporting
confidence: 93%
“…Mlc2v cre :Ect2 flox/flox mutants had an increase in the mean ratio of BiNucs to MoNucs at P3 of 0.901 ± 0.08 compared to 0.339 ± 0.02 in control mice ( Figures 7C and 7D). This result agrees with recent work by Liu et al (2019), which also showed that the loss of Ect2 results in an increase in BiNucs during the neonatal period and that increased expression of Ect2 leads to increased MoNucs. qPCR revealed a significant decrease in the expression of E2f target genes in Mlc2v cre : Ect2 flox/flox mutants compared to controls, but no significant change in genes that are not E2f targets ( Figure 7E).…”
Section: Binucleation Directly Results In the Downregulation Of E2f Tsupporting
confidence: 93%
“…In conclusion, the recently published data about the impact of propranolol on increased cytokinesis failure in congenital heart disease from H. Liu et al [1] together with our data who show myocardial protection by the decrease of cTnT after propranolol or carvedilol treatment are very important to increase the acceptance of early beta blocker therapy in infants with heart failure and other infants who suffer from early life stress to improve longtime cardiovascular health.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, H. Liu et al showed that treatment with non-selective beta blockers early after birth might rescue cytokinesis defects in infants with congenital heart defects and prevent heart dysfunction in adulthood in a mouse model [1].…”
Section: Introductionmentioning
confidence: 99%
“…Signaling through adrenergic receptors reportedly modulates various cellular functions or properties, including (but not limited to) cell cycle and proliferation ( 91 , 92 ), migration ( 93 ), and cytokine ( 94 ) and antibody ( 95 ) production. Although historically, signaling through β-ARs has often been associated with anti-inflammatory outcomes, in more recent years, the ability of β-ARs to mediate context-dependent, pro- and anti-inflammatory effects has become more widely appreciated ( 29 , 94 , 96 ).…”
Section: Circadian Rhythms and The Adrenergic Systemmentioning
confidence: 99%